Os impactos da pandemia da Covid-19 no acesso de pessoas físicas à Bovespa: uma análise econométrica - Lima, Carlos Alexandre de Souza (2022)
The present study to analyze the access of individuals to the Ibovespa, based on the analysis of the impacts of the COVID 19 pandemic on the economy. Therefore, a literature review was carried out with the aim of identifying the main variables that explain this phenomenon. Subsequently, an econometric regression was performed to estimate the parameters of the effects and variables chosen to measure the impact of the COVID 19 pandemic on the access of individuals to Bovespa.